(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Supercooling effects of novel Phase Change Materials microcapsules incorporated with silver nano particles (NC-MicroPCMs) and conventional PCM microcapsules (MicroPCMs) are compared and evaluated systematically. Melting and crystallization behaviors of microcapsules with different processing parameters are investigated mainly by DSC measurements. Combinations of processing parameters are determined by a full factorial experimental design. The influences of processing parameters are discussed and analyzed by statistical softwares of SPSS and Minitab. The results have shown that the formation of nano composite structure can reduce the effect of supercooling. The possible mechanisms have also been explored.